Suspected Heroin Overdoses in US Emergency Departments, 2017–2018 - Vivolo-Kantor, Alana Marie (Am J Public Health, 2019)
Objectives. To describe changes in suspected heroin overdose emergency department (ED) visits. Methods. We analyzed quarterly and yearly changes in heroin overdoses during 2017–2018 by using data from 23 states and jurisdictions (including the District of Columbia) funded by the Centers for Disease Control and Prevention Enhanced State Opioid Overdose Surveillance program. The analyses included the Pearson χ(2) test to detect significant changes. Results. Both sexes, all age groups, and some states exhibited increases from quarter 1 (Q1) 2017 to Q2 2017 and significant decreases in both quarters from Q3 2017 to Q1 2018 in heroin overdose ED visits. Overall, there was a significant yearly decline of 21.5% in heroin overdose ED visits. Three states had significant yearly increases (Illinois, Indiana, and Utah), and 9 states (Kentucky, Maryland, Massachusetts, New Hampshire, Ohio, Pennsylvania, Rhode Island, West Virginia, and Wisconsin) and the District of Columbia had significant decreases. Conclusions. We identified decreases in heroin overdose ED visits from 2017 through 2018, but these declines were not consistent among states. Even with the possibility of a stabilization or slowing of this epidemic, it is important that the field of public health and its partners implement strategies to prevent overdoses and target emerging hot spots.